Oxidative Stress and TGF-β1/Smads Signaling Are Involved in Rosa roxburghii Fruit Extract Alleviating Renal Fibrosis. (20th August 2019) - Zhan, Jihong; Liu, Mingjie; Pan, Lijun; He, Liqun; Guo, Yinxue
Abstract : Fibrosis is involved in the pathogenesis of kidney diseases. We previously discovered that Rosa roxburghii fruit (Cili) possesses antifibrosis property in chronic renal disease, but the mechanisms are unknown. We hypothesized that Cili might prevent fibrosis development through mediating TGF- β /Smads signaling, which is known to be involved in renal fibrosis. This study aimed to confirm the effects of freeze-dried Cili powder in a rat model of unilateral ureteral obstruction (UUO) and examine TGF- β /Smads signaling. Rats were randomized to (n=12/group): sham operation, UUO, UUO with losartan, UUO with moderate Cili dose (3 g/kg/d), and UUO with high Cili dose (6 g/kg/d). The rats were sacrificed after 14 days of treatment. Collagen deposition was tested using Masson's staining. TGF- β /Smads signaling was examined by qRT-PCR, western blot, and immunohistochemistry. Rats in the UUO group showed excessive deposition of collagen in kidney interstitium, accompanied with high levels of renal 8-hydroxy-2′-deoxyguanosine, renal malondialdehyde, blood urea nitrogen (BUN), serum creatinine (Scr), and proteinuria (all P<0.05). Cili powder efficiently alleviated the pathological changes and oxidative stress in the kidneys of UUO rats, and decreased BUN, Scr and proteinuria (all P<0.05). Cili powder also inhibited the upregulation of TGFB1, TGFBR1, TGFBR2, SMAD2, and SMAD3 and reversed the downregulation of SMAD7 in obstructed kidneys (mRNA and protein) (all P<0.05). In summary, the results suggest that Cili freeze-dried powder effectively prevents renal fibrosis and impairment in UUO rats, which is associated with the inhibition of oxidative stress and TGF- β 1/Smads signaling.